2010
DOI: 10.2169/internalmedicine.49.3135
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with Rituximab in a Patient with TTP Secondary to Severe ANCA-Associated Vasculitis

Abstract: We report a case of thrombotic thrombocytopenic purpura (TTP) secondary to antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis treated by rituximab. TTP secondary to ANCA-associated vasculitis is very rare and has a high mortality rate. We employed rituximab and successfully treated TTP secondary to ANCA-associated vasculitis, because standard therapies, such as steroid therapy, intravenous pulse cyclophosphamide, and repeated plasma exchange (PE), did not suppress her disease activity. This is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…However, the prevalence in other countries is unclear, especially for renal TMA in ANCA-associated GN. As reported in previous case reports, patients with concomitant renal TMA in ANCA-associated GN presented with more severe renal injury (3)(4)(5)(6)(7)(8)(9). Patients with renal TMA in our cohort also had a higher level of initial serum creatinine, higher percentage of cellular crescents and fibrinoid necrosis, and more severe interstitial infiltration compared with patients without TMA, which, by a large cohort study, further extends previous findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the prevalence in other countries is unclear, especially for renal TMA in ANCA-associated GN. As reported in previous case reports, patients with concomitant renal TMA in ANCA-associated GN presented with more severe renal injury (3)(4)(5)(6)(7)(8)(9). Patients with renal TMA in our cohort also had a higher level of initial serum creatinine, higher percentage of cellular crescents and fibrinoid necrosis, and more severe interstitial infiltration compared with patients without TMA, which, by a large cohort study, further extends previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, TMA in ANCA-associated GN has only been reported in isolated case reports (3)(4)(5)(6)(7)(8)(9), with two patients showing pathologic features of renal TMA. The clinicopathologic characteristics, especially the prognostic value of pathologic findings of renal TMA, in ANCA-associated GN are far from clear.…”
Section: Introductionmentioning
confidence: 98%
“…Several reports in the literature have clearly shown that rituximab, an anti-CD20 chimeric monoclonal antibody, is highly efficient as an adjunctive therapy for TTP patients who do not respond adequately to a standard combination therapy of PE and steroids (29)(30)(31). Globally, the on-label therapeutic use of rituximab is for CD20-positive malignant B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…TPE (16 sessions) and prednisolone slowly corrected her thrombocytopenia and the need for hemodialysis support in association with improvement in ADAMTS13 activity level (from 27% to 68%, ADAMTS13 antibodies not reported). The third case report described a 66-year-old woman with known MPO-antibody vasculitis on maintenance prednisolone therapy, who was hospitalized with acute vasculitic features, worsening renal function, and TTP [14]. Her ADAMTS13 levels were reported to be decreased (37.8%), but no inhibitory antibodies were detected.…”
Section: Discussionmentioning
confidence: 99%